AKIBAT HUKUM PEMBATALAN PENDAFTARAN MEREK TERHADAP HAK PENERIMA LISENSI MEREK MENURUT UU NO. 15 TAHUN 2001 - Mardianto, Agus (Jurnal Dinamika Hukum, 2011)
Trade globalization has made trade mark becomes very important, especially in relation to a fair business competition. A trade mark is a sign that functions as a distinguished from those of others, quality guarantee and source of origin.  Owner of a trade mark registered reserves exclusive right to use that trade mark for a period of time or may grant permission to other parties to use the trade mark.  Permission to other parties should be given through a letter of agreement for permission to use (not transfer of ownership) that trade mark for a certain period of time, and this is accordingly called licence.  Registration of a trade mark in the general list of trade mark can be cancelled upon request with an argument that the trade mark has a basic similarity with a previously registered trade mark, or the registration was made for cruel intention.  This paper discusses licence and cancellation of a trademark, as well as the consequences of trade mark cancellation for the licensee. Cancellation of a trade mark registration results in termination of a trade mark license agreement, but the licensee may reserve his right until the completion of agreement period.Key words : exclusive right, license agreement, licensee